Sustainable land management and implications on incomes, food self-sufficiency and women - Bwalya, Bridget; Mutandwa, Edward; Chiluba, Brian Chanda (Frontiers in Sustainable Food Systems, 2024)
The adoption of Sustainable Land Management (SLM) practices among smallholder farmers remains low, particularly among women farmers. Understanding the relationship between assets, gender, and SLM adoption and how their interaction impinges on household food self-sufficiency and livelihoods is essential for developing gender-responsive SLM programmes that effectively promote sustainable livelihoods and address household food insecurity. This study examines the effects of asset type on SLM practices adoption, women farmers, and their implications on household incomes and food self-sufficiency. Data was collected through a cross-sectional survey of 761 households selected from 11 chiefdoms across six districts in Eastern Zambia. Analysis involved Structural Equation System framework and Propensity Score Matching techniques to examine relationships between SLM adoption, food self-sufficiency, and household incomes, considering various socio-economic factors. Results showed marital status and household size as significant demographics, with education positively correlating with household income and SLM participation (p < 0.05). Gender disparities persisted, with male-headed households having higher incomes. Labour allocation analysis revealed women’s involvement in labour-intensive tasks, while smaller farms showed higher income probabilities, supporting sustainable agricultural intensification. Social capital significantly influenced SLM participation, and access to financial capital. Livestock assets, land size, and crop diversity predicted food security, while male decision-making influenced food security and income. Incomes were higher for women participating in SLM projects. This study underscores the importance of SLM practices in influencing household incomes and food security, especially for women. Addressing gender disparities and promoting women’s empowerment in agriculture are crucial for achieving equitable and sustainable rural development. Policymakers can foster sustainable livelihoods in rural communities by prioritizing SLM and empowering women.